Economic Perspective in the Production of Magnetite (Fe3O4) Nanoparticles by Co-precipitation Method - Prabowo, Bagas; Khairunnisa, Thiya; Nandiyanto, Asep Bayu Dani (World Chemical Engineering Journal, 2018)
Magnetite contains both types of iron namely ferrous and ferric, so it is usually described as IronII, III Oxide. Nano-sized Magnetite (Fe3O4) not only increases lattice parameters and unit cell volumes but also the effective area and surface area have definitely increased. Magnetite can improve the electrical properties of a polymeric material through the copolymers synthesis method. Therefore, there is a need for the feasibility study for generating industries for the production of Fe3O4 especially in the developing countries. This study aimed to evaluate the prospect for the production of iron oxide (Fe3O4) nanoparticles in practical uses. This study was done to confirm whether the large-scale production of Fe3O4 is profitable or not. The evaluation was done using two types of feasibility studies: engineering analysis and economic evaluation. The estimation of the project was also completed with the calculation from ideal conditions to the worst cases of production from changes of raw material prices. The engineering analysis gave information the potential large-scale production since the process can be applied using commercially available and inexpensive apparatuses. The economic evaluation based on various economic evaluation parameters (such as gross profit margin, break-even point, payback period, etc) showed the potential profitability for the project. All evaluation parameters gave positive points. The project also used relatively inexpensive total cost of purchased equipment. Although further developments must be also added especially regarding the additional strategies to boost the profit to attract the investors, this study provides a quite promise for the possible fabrication of Fe3O4 in developing countries.